Tsetse control: Recent successes in Tanzania and Ethiopia - Vreysen, M.J.B.; Leak, S.G.A. (1996)
Trypanosomiasis remains the most important constraint to livestock production on the African continent. Chemotherapy, using curative and prophylactic drugs, is the main method of control of the disease in cattle. The exploitation of the trypanotolerance trait of some breeds of large and small ruminants provides a solution in certain production systems. Immunological approaches to control the disease through vaccination are still under investigation. Only the eradication of the tsetse fly vector can remove the treat of the disease. By coincidence two biologists defended their PhD theses on aspects of tsetse control almost at the same time at two universities in The Netherlands. On 19 December, 1995, Marc Vreysen from Belgium defended his thesis entitled: 'Radiation induced sterility to control tsetse flies. The effect of ionising radiation and hybridisation on tsetse biology and the use of the sterile insect technique in integrated tsetse control' at Wageningen Agricultural University. Three months later, on 22 February, 1996, Stephen Leak from the UK defended his thesis: 'A contribution to the epidemiology and understanding of tsetse-transmitted trypanosomiasis' at Utrecht University. In this article some of the results of these studies will be discussed. Emphasis will be on the applications of the control measures under field conditions at the respective study locations: Unguja island of Zanzibar, Tanzania and the Ghibe Valley in Ethiopia. For further reading a list of references is provided and readers who are interested in more details are invited to write to the authors.